On some inequalities for generalized s-convex functions and applications on fractal sets - Kilicman, Adem; Saleh, Wedad (International Scientific Research Publications, 2017)
The authors present some new inequalities of generalized Hermite-Hadamard’s type for the class of functions whose second local fractional derivatives of order α in absolute value at certain powers are generalized s-convex functions in the second sense. Moreover, some applications are given.